Technical Trading ETFs in the 21st Century - Garza-Gomez, Xavier; Metghalchi, Massoud (Journal of Applied Business and Economics, 2023)
This paper tested the effectiveness of the popular trading rule based on the 50-day and 200-day moving averages on two ETFs: QQQ and SPY using daily and weekly data. We find that for both weekly and daily data, the trading rule shows good results for the entire sample. When we introduce subperiods by decades, we find that the technical rules only work around 50% of the time. When we explored the performance on shorter subperiods of 2.5 years, we found a strong correlation between realized volatility (standard deviation of returns) and the performance of active strategies. To take advantage of this correlation, we modified the basic moving average strategy so we will be invested in the asset when volatility is low but will employ the MA trading rule when volatility increases. We find that the performance of active strategies improved when volatility is considered. Overall evidence in this paper supports the continued usage of technical analysis as a protective tool for high volatility periods.